Biathlon injury and Illness Surveillance project (BIIS): development of biathlon-specific surveillance forms in English, Russian, French and German - Van Dyk, C.; Perera, N. P.; Carrabre, J. E.; Manfredini, F.; Fitzpatrick, J. (BMJ Open Sport & Exercise Medicine, 2019)
Objective The aim of this project was to adapt the English, French, German and Russian versions of the International Olympic Committee (IOC) injury and illness surveillance form to be sport-specific for use in biathlon.